2013
DOI: 10.1038/bjc.2013.320
|View full text |Cite
|
Sign up to set email alerts
|

miR-320c regulates gemcitabine-resistance in pancreatic cancer via SMARCC1

Abstract: Background:Gemcitabine-based chemotherapy is the standard treatment for pancreatic cancer. However, the issue of resistance remains unresolved. The aim of this study was to identify microRNAs (miRNAs) that govern the resistance to gemcitabine in pancreatic cancer.Methods:miRNA microarray analysis using gemcitabine-resistant clones of MiaPaCa2 (MiaPaCa2-RGs), PSN1 (PSN1-RGs), and their parental cells (MiaPaCa2-P, PSN1-P) was conducted. Changes in the anti-cancer effects of gemcitabine were studied after gain/lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(69 citation statements)
references
References 48 publications
2
65
1
1
Order By: Relevance
“…And miR-320b was reported to regulate cell-surface ICAM-1 expression on endothelial cells29. Moreover, abnormal expression of miR-320a was found in multiple malignancies including pancreatic cancer30313233 and miR-320c modulated the gemcitabine-resistance of pancreatic cancer cells through SMARCC134. The miR-320s have been shown to be dysregulated in insulin resistance, fibrosis, and pancreatic malignancies, which indicated they played pivotal roles in the development and/or complications of CP.…”
Section: Discussionmentioning
confidence: 99%
“…And miR-320b was reported to regulate cell-surface ICAM-1 expression on endothelial cells29. Moreover, abnormal expression of miR-320a was found in multiple malignancies including pancreatic cancer30313233 and miR-320c modulated the gemcitabine-resistance of pancreatic cancer cells through SMARCC134. The miR-320s have been shown to be dysregulated in insulin resistance, fibrosis, and pancreatic malignancies, which indicated they played pivotal roles in the development and/or complications of CP.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that upregulated ADAM17 expression resulted in decreased E-cadherin expression and evaluated N-cadherin and Vimentin expression, suppressed ADAM17 expression resulted in increased E-cadherin expression and decreased N-cadherin and Vimentin expression, which suggested that ADAM17 could affect EMT. miRNAs bind target mRNAs at complementary sites in their 3'-untranslated regions (3'-UTRs), thereby suppressing the expression of the target gene at the posttranscriptional level [19][20][21]. Through this mechanism, miRNAs regulate a wide range of biological processes, including cell proliferation and differentiation [22], migration, apoptosis, development, and metabolism [23][24][25].…”
Section: Down-regulation Of Adam17 By Sirna Reversed the Effect Of MImentioning
confidence: 99%
“…This study concluded that miR-142-5p is a predictive marker for gemcitabine responsivness in patients with resected pancreatic cancer. miR-320c is also found to be significantly overexpressed in gemcitabine-resistant pancreatic cancer cells suggesting its potential use as a marker for predicting clinical response [66]. Yu J et al [67] showed that patient group exhibiting high miR-200c expression had median survival of 33.5%, while it was only 11.2% in the patient group with low miR-200c expression.…”
Section: Clinical Potential Of Mirnas In Pancreatic Cancermentioning
confidence: 99%